A new cracking resistance index based on fracture mechanics for high strength sheet metal ranking. Issue 1 (June 2021) - Frómeta, D.; Parareda, S.; Lara, A.; Grifé, L.; Tarhouni, I.; Casellas, D.
Abstract: Driven by current safety and weight reduction policies in the automotive sector, the development of new high strength sheet metal products has experienced unprecedented growth in the last years. With the emergence of these high strength materials, new challenges related to their limited ductility and higher cracking susceptibility have also raised. Accordingly, the development of new fracture criteria accounting for the material's cracking resistance has become unavoidable. In this work, a new cracking resistance index (CRI) based on fracture mechanics is proposed to classify the crack propagation resistance (i.e. the fracture toughness) of high strength metal sheets. The index is based on the fracture energy obtained from tensile tests with sharp-notched specimens. The procedure is very fast and simple, comparable to a conventional tensile test, and it may be used as routine testing for quality control and material selection. The CRI is investigated for several advanced high strength steel (AHSS) sheets of 0.8-1.6 mm thickness with tensile strengths between 800 and 1800 MPa. The results show that the proposed index is suitable to rank high strength steel sheets according to their crack propagation resistance and it can be correlated to the material's crashworthiness and edge cracking resistance.